Pedagogical Value of Didactic Audiovisual Translation through English Language Learners’ perceptions - Sabate-Carrove, Mariona; Couto-Cantero, Pilar; Tinedo-Rodríguez, Antonio-Jesús (Complutense Journal of English Studies, 2025)
This paper assesses the validity of various modes of didactic audiovisual translation (DAT) in supporting foreign language learning, with a focus on a project conducted throughout 2022 and 2023. Fifty-five participants completed a comprehensive set of tasks, including an Initial Test of Integrated Skills (ITIS), a Final Test of Integrated Skills (FITIS), and a series of 30 piloted lesson plans—15 for B1 and 15 for B2 levels. These lesson plans followed a task-based learning structure and were designed around five modalities: subtitling, voice-over, dubbing, audio description, and SDH, in line with the methodological framework proposed by Talaván and Lertola (2022). Our findings suggest that all DAT modes contributed comparably to the development of language skills, linguistic components, and cross-curricular competences. Notably, revoicing techniques were perceived as particularly beneficial for enhancing oral skills. Participants reported high levels of engagement with the DAT-based project and expressed strong support for its recommendation to other language learners. Although some technical challenges were noted, participants also identified secondary gains in ICT skills. The study offers promising insights into the pedagogical value of DAT methodologies for comprehensive language learning.